Gut Microbiota in Adipose Tissue Dysfunction Induced Cardiovascular Disease: Role as a Metabolic Organ - Yang, Xinyu; Zhang, Xianfeng; Yang, Wei; Yu, Hang; He, Qianyan; Xu, Hui; Li, Shihui; Shang, Zi'ao; Gao, Xiaodong; Wang, Yan; Tong, Qian (Frontiers in Endocrinology, 2021)
The gut microbiome has emerged as a key regulator of host metabolism. Accumulating evidence has indicated that gut microbiota is involved in the development of various human diseases. Such connection relies on the structure and metabolites of gut microbiota. Gut microbiota metabolizes the diet ingested by the host into a series of metabolites, including short chain fatty acids, secondary bile acid, trimethylamine N-oxide, and branched-chain amino acids, which affects the host physiological processes by activation of numerous signaling pathways. In this review, we first summarize the various mechanisms through which the gut microbiota influences adipose tissue dysfunction and metabolic processes that subsequently cause cardiovascular diseases, highlighting the complex interactions between gut microbes, their metabolites and metabolic activity of host. Furthermore, we look into the current status of clinical therapies for adipose tissue dysfunction aiming gut microbiota. Finally, we discuss the challenges that remain to be met before this field of research can generate knowledge which can impact everyday clinical practice.